Peran Kepala Sekolah dalam Pengelolaan Dana BOSP untuk Pengembangan Sarana Prasarana - Reski Ramadhan; Anggra Prima (BEduManagers Journal : Borneo Educational Management and Research Journal, 2026)
This study aims to describe the principal's role in managing the School Operational Assistance Fund (BOSP) for the development of educational facilities and infrastructure at SD Negeri 012 Bengalon. This research employed a qualitative approach using a case study design. Data were collected through observation, interviews, and documentation involving the principal, school treasurer, teachers, and other related parties. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings revealed that the principal played an active role in planning, implementing, supervising, and evaluating the utilization of BOSP funds. Fund management was carried out through the preparation of the School Activity and Budget Plan (RKAS) based on priority needs and contributed to the development of facilities and infrastructure, maintenance of school facilities, and provision of learning media. The main challenges included budget limitations and increasing infrastructure needs. Solutions involved priority-based budgeting, optimization of fund utilization, and strengthening transparency and collaboration with stakeholders.